First-order phase transition of the vortex lattice in twinned YBa2Cu3O7 single crystals in tilted magnetic fields - Nieva, Gladys; Maiorov, B.; Nieva, G.; Osquiguil, E. (American Physical Society, 2000)
Fil: Maiorov, B. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina